Umbilical Cord Mesenchymal Stem Cells Promoting Spinal Cord Injury Repair Visually Monitored by AIE‐Tat Nanoparticles. Issue 12 (14th September 2022) - Xie, Peigen; Ling, Haiqian; Pang, Mao; He, Lei; Zhuang, Zeyan; Zhang, Guiling; Chen, Zihao; Weng, Chuanggui; Cheng, Sijin; Jiao, Ju; Zhao, Zujin; Tang, Ben Zhong; et al.
Abstract: Spinal cord injury (SCI) is a severe body trauma that can cause permanent loss of somatic nerve function and lacks effective treatment. Transplantation of stem cells is a promising therapeutic approach for SCI but faces with the difficulty of long‐term tracking of stem cells in vivo precisely. Herein, this work wishes to report a kind of umbilical cord mesenchymal stem cells (UC‐MSCs) labeled with aggregation‐induced emission (AIE)‐Tat nanoparticles (NPs) for tracing the repair and treatment of SCI. These AIE‐Tat NPs have strong fluorescence, good biocompatibility, and long‐term tracking ability with a high signal‐noise ratio. The labeling of AIE‐Tat NPs does not induce adverse effects on the activity and performance of UC‐MSCs. The fluorescence signal of the UC‐MSCs can be monitored for up to 28 days, reflecting the viability, colonization, and function of the transplanted UC‐MSCs. The transplantation of UC‐MSCs can secrete nerve growth factors and maintain the viability of cells in the highly reactive oxygen species microenvironment, leading to effective recovery of injured spinal cord, which is further confirmed by the behavioral rehabilitation and histopathological results. These findings demonstrate that long‐term tracking of UC‐MSCs labeled with AIE‐Tat NPs is a promising method to monitor stem cell transplantation therapy for SCI. Abstract : Aggregation‐induced emission ‐Tat nanoparticle‐labeled umbilical cord mesenchymal stem cells are transplanted into the spinal cord‐injured rats for the long‐term and real‐time monitoring of stem cell transplantation therapy, visually providing important information of the viability, colonization, and function of the transplanted stem cells.